2008
DOI: 10.1007/s11694-008-9052-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical scattering in beef steak to predict tenderness using hyperspectral imaging in the VIS-NIR region

Abstract: The objective of this research is to develop a non-destructive method for predicting cooked beef tenderness using optical scattering of light on fresh beef muscle tissue. A hyperspectral imaging system (k = 496-1,036 nm) that consists of a CCD camera and an imaging spectrograph, was used to acquire beef steak images. The hyperspectral image consisted of 120 bands with spectral intervals of 4.54 nm. Sixty-one fresh beef steaks, including 44 strip loin and 17 tenderloin cuts, were collected. After imaging, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 27 publications
0
19
1
2
Order By: Relevance
“…It was successfully implemented for predicting beef tenderness (Cluff et al, 2008;Peng and Wu, 2008), classification and prediction of marbling, colour, texture and exudation, drip loss, pH in pork (Qiao et al, 2007a,b,c), contaminants and tumor detection in chicken (Lawrence et al, 2004;Nakariyakul and Casasent, 2004;Park et al, 2006) and assessment of water and fat contents in fish fillets (ElMasry and Wold, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was successfully implemented for predicting beef tenderness (Cluff et al, 2008;Peng and Wu, 2008), classification and prediction of marbling, colour, texture and exudation, drip loss, pH in pork (Qiao et al, 2007a,b,c), contaminants and tumor detection in chicken (Lawrence et al, 2004;Nakariyakul and Casasent, 2004;Park et al, 2006) and assessment of water and fat contents in fish fillets (ElMasry and Wold, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near infrared (Vis/NIR) hyperspectral imaging (400e1000 nm) has also been widely applied to determine the tenderness of meats. Seven key wavelengths (501, 510, 646, 651, 927, 1005 and 1023 nm) were identified by SR to predict WBSF scores of fresh beef (Cluff et al, 2008). Similarly, for prediction of beef WBSF, the MLR model was based on the selected eight wavelengths (485, 524, 541, 645, 700, 720, 780 and 820 nm) by SR and gave R cv ¼ 0.91 .…”
Section: Feature Wavelengths For Predicting Quality Attributesmentioning
confidence: 99%
“…The authors defined SSF ≤ 205.8 N as tender meat,SSF between 205.8 and 254.8 N as intermediate,and SSF > 254.8 N as tough meat. In a similar study, a hyperspectral imaging system (496 to 1036 nm) was used to measure the tenderness of beef (Cluff et al, 2008). The authors reported fitting the optical scattering profiles obtained from the hyperspectral images using a modified Lorentzian function.…”
Section: Beefmentioning
confidence: 99%